Parasocial Relationships: Players' Emotional Attachment to Characters in the Otome Game Love and Deepspace - Natasha Narwastu Kurnianto, Yobelinda (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores player character attachment in the otome mobile game Love and Deepspace and its impact on their lived experiences. Using a literature review approach, this study highlights how parasocial interactions with the main character and love interests affect players' emotional, social, and behavioral aspects. Results indicate that character attachment can increase emotional well-being, strengthen social relationships, and motivate positive behaviors in daily life, despite the risk of overspending. These findings provide a basis for further research into the psychological and social effects of mobile games, particularly otome games, on players.